THE EFFECT OF CASH FLOW AND RETURN ON EQUITY ON RETURN ON INVESTMENT BASED ON FOOD AND BEVERAGES SECTOR COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2019 – 2021 - Putri, Aliya Ananda; Zulkifli, Zulkifli (PERFECT EDUCATION FAIRY, 2023)
This study aims to determine the effect of Cash Flow and Return on Equity (ROE) on Return on Investment (ROI) in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2019- 2021 period. The population of this study amounted to 72 companies. The sampling technique using the sampling method obtained 26 companies. The results of the study prove that Cash Flow has no significant effect on Return on Investment (ROI). Meanwhile, Return on Equity (ROE) has a positive and significant effect on Return on Investment (ROI) in food and beverages sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period.